Raíces adventicias de Saxegothaea conspicua Lindl. (Podocarpaceae) en su etapa de senescencia en bosques adultos - CANO, MAURICIO J.; GODOY, ROBERTO; SOTO, DANIEL P. (Gayana Botánica, 2014)
We studied the anatomy of the adventitious structures that Saxegothaea conspicua Lindl. develops inside of the stem during its senescence stages in old-growth temperate forest; by scanning electronic microscopy, we evaluated the hypothesis whether those structures correspond to adventitious roots. The results confirm that the anatomical structures are similar to a common roots system at first development stages. We discuss the possible functional implications of these adventitious roots in extend the life of the individuals in forests.